Diffusion and defect reactions in isotopically controlled semiconductors - Bracht, Hartmut (Diffusion Fundamentals, 2008)
Point defects in semiconductors play a decisive role for the functionality of semiconductors. A detailed, quantitative understanding of diffusion and defect reactions of dopants is required for advanced modelling of modern nanometer size electronic devices. With isotope heterostructures which consist of epitaxial layers of isotopically pure and deliberately mixed stable isotopes, we have studied the simultaneous self- and dopant diffusion in several major semiconductors such as silicon and germanium. Detailed analysis of the simultaneous diffusion of self- and dopant atoms in Si and Ge yields information about the ionization levels of native defects and about dopant-defect interactions in Si and Ge. The results of these diffusion studies are highlighted in this work.